2001
DOI: 10.1046/j.1365-3180.2001.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of uprooting and soil‐covering on the effectiveness of weed harrowing

Abstract: The impact of uprooting and covering plants on mortality and growth reduction was investigated in the laboratory using Lolium perenne L. and Lepidium sativum L. (harrowed 3–4 days after emergence) and Chenopodium quinoa Willd. (harrowed at emergence) as model weed species. Although the predominant initial effect of harrowing was to cover the plants, only 1–17% of the non‐uprooted covered plants were killed because the depth at which they were buried by the harrow was shallow. Uprooting was more effective (47–6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 15 publications
7
78
0
3
Order By: Relevance
“…It tills the soil surface superficially, so that weed seedlings are uprooted and covered by soil. Some authors have suggested that the most important effect is covering (Jones et al, 1995), while in other experiments uprooting was probably the main cause (Kurstjens and Kropff, 2001;Cirujeda et al, 2003). Uprooting and covering may not completely kill the weeds, but the damage caused may be enough to slow down their growth (Lambain et al, 1993) although Rasmussen (1992) did not find that surviving weeds had a lower competitive ability.…”
Section: Introductionmentioning
confidence: 99%
“…It tills the soil surface superficially, so that weed seedlings are uprooted and covered by soil. Some authors have suggested that the most important effect is covering (Jones et al, 1995), while in other experiments uprooting was probably the main cause (Kurstjens and Kropff, 2001;Cirujeda et al, 2003). Uprooting and covering may not completely kill the weeds, but the damage caused may be enough to slow down their growth (Lambain et al, 1993) although Rasmussen (1992) did not find that surviving weeds had a lower competitive ability.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, additional conditions for application (e.g., temperature, soil moisture, soil texture) have to be satisfied in comparison to chemical approaches. The strong dependency on weather conditions for mechanical weed control has already been shown in Kurstjens and Kropff [30]. Therefore, if mechanical weed control is not applicable or successful, an additional cost-effective chemical measure is necessary.…”
Section: Weed Densitymentioning
confidence: 95%
“…These tools can be used to perform a whole crop cultivation (crop and weed plants), inter-row and intra-row cultivation. Cultivating tillage mainly controls annual weeds through uprooting, tearing plants into pieces and burial of weeds into soil; however perennial weeds are little affected (Jensen et al, 2004;Kurstjens & Kropff, 2001;Kurstjens & Perdok, 2000;Rueda et al, 2010). Since controlling weeds with mechanical tools generally is a trade-off between weed control and crop damage due to cultivation, post-emergence cultivation must be combined with pre-emergence methods to overcome the poor selectivity (Melander et al, 2005).…”
Section: Mechanical Weeding (Harrowing)mentioning
confidence: 99%